EXPANDING THE CRITERIA FOR SELECTION OF DONOR HEARTS USING NORMOTHERMIC REGIONAL PERFUSION IN BRAIN-DEAD DONORS - Сhaikovska Sofia; Sudakevych, Serhii; Todurov, Borys; Falk, Christine S.; Kovtun, Gavrylo; Kuzmych, Igor; Melnyk, Mykola; Taranov, Maxim; Shpachuk, Anton (Eastern Ukrainian Medical Journal, 2025)
Background. Heart transplantation is a life-saving procedure for patients with end-stage heart failure. The critical shortage of donor organs, martial law in Ukraine causes to expand the criteria for selecting donor hearts using the so-called "marginal donors." Due to the use of marginal donor heart can increase the donor organ pool by 40%. Methods. We made a retrospective analysis of 12 cases of heart transplantation performed by the heart transplantation team of the State Institution "Heart Institute of the Ministry of Health of Ukraine" in 2012-2023, during which normothermic regional perfusion was used for donor preconditioning. Results. We performed 106 heart transplants from donors with confirmed brain death. In 12 (11.3%) cases, normothermic regional perfusion was used for donor preconditioning. The total duration of normothermic regional perfusion was 124.5±10.1 minutes. All donors had metabolic acidosis, hyperkalemia, and hyperlactatemia before the NRP initiation. The use of normothermic regional perfusion was characterized by normalization of the acid-base state, a significant increase in pH (p<0.001), a significant elimination of base deficiency (BE) (p<0.001) and an increase in HCO3- (p<0.001). There was also a significant increase in pO2 (p<0.001) and a decrease in pCO2 (p<0.001). Moreover, the use of NRP significantly reduced the baseline levels of lactate from 10.4±2.91 mmol/L to 1.57±0.33 mmol/L (p<0.001) and potassium (p=0.003). Conclusion. Our study showed that the use of normothermic regional perfusion in brain-dead donors was characterized by normalization of water-electrolyte and acid-base disorders, reduced need for norepinephrine to maintain mean arterial pressure above 50 mm Hg, and a one-year survival rate of 75.0%.